ANALISIS RENTABILITAS, FAKTOR-FAKTOR PRODUKSI USAHA PEMBUATAN TEMPE, DAN TATANIAGANYA DIKECAMATAN SUKARAJA - Nusril, Nusril; Nurung, M; Zuardi, Zuardi (Jurnal AGRISEP, 2004)
This study  was  aimed  at  analysis rentability  factors  influencing production, investigating marketing channel of tempe industry in District of Sukaraja. Samples were selected purposively, i.e. small medium and large tempe industry which is measured for its omset.  For marketing channel analysis, puspose,.entrepreneu(retailer  were taken while dealer, were selected using simple random sampling. Profit  and gross  margin ratio  were used to  analyze industry rentability while C-D  and marketing margin were used for analyze second and third purpose. The research show that Tempe Industry in Sukaraja District were able to gain profIt. Furthermore, volume of soybean, labor, other input where significant influencing tempe production. For marketing channel were founded on research location with 72.52%  of margin was a/located for producers.